A Novel G16B09-Like Effector From Heterodera avenae Suppresses Plant Defenses and Promotes Parasitism - Yang, Shanshan; Dai, Yiran; Chen, Yongpan; Yang, Jun; Yang, Dan; Liu, Qian; Jian, Heng (Frontiers in Plant Science, 2019)
Plant parasitic nematodes secrete effectors into host plant tissues to facilitate parasitism. In this study we identified a G16B09-like effector protein family from the transcriptome of Heterodera avenae, and then verified that most of the members could suppress programmed cell death triggered by BAX in Nicotiana benthamiana. Ha18764, the most homologous to G16B09, was further characterized for its function. Our experimental evidence suggested that Ha18764 was specifically expressed in the dorsal gland and was dramatically upregulated in the J4 stage of nematode development. A Magnaporthe grisea secretion system in barley showed that the signal peptide of Ha18764 had secretion activity to deliver mCherry into plant cells. Arabidopsis thaliana overexpressing Ha18764 or Hs18764 was more susceptible to Heterodera schachtii. In contrast, BSMV-based host-induced gene silencing (HIGS) targeting Ha18764 attenuated H. avenae parasitism and its reproduction in wheat plants. Transient expression of Ha18764 suppressed PsojNIP, Avr3a/R3a, RBP-1/Gpa2 and MAPK kinases (MKK1 and NPK1Nt)-related cell death in Nicotiana benthamiana. Co-expression assays indicated that Ha18764 also suppressed cell death triggered by four H. avenae putative cell-death-inducing effectors. Moreover, Ha18764 was also shown strong PTI suppression such as reducing the expression of plant defense-related genes, the burst of reactive oxygen species, and the deposition of cell wall callose. Together, our results indicate that Ha18764 promotes parasitism, probably by suppressing plant PTI and ETI signaling in the parasitic stages of H. avenae.